MANAJEMAEN PENGELOLAAN PERAN KODIM 0705/MAGELANG DALAM MENINGKATKAN NASIONALISME DAN ANIMO MASUK TNI PADA GENERASI MUDA DI MAGELANG - Basuki, Aris; Suluh Usada Adi; Yulianto; Reza Yudha P; Raehan Aditia W (JURNAL MAHATVAVIRYA, 2024)
The existence of the territorial command function placed in each city and district area to fulfil what is expected so far for the love of the homeland, so this research was conducted with the aim of knowing the role of Kodim 0705 / Magelang among the younger generation and what obstacles faced by Kodim 0705 / Magelang personnel and other small territorial ranks that can hinder the course of increasing nationalism in the younger generation among these students. Another goal is to find out what efforts are implemented by Kodim 0705/Magelang in increasing nationalism among these students. This research is a descriptive qualitative research with data collection techniques using interview methods, observation and documentation. The results of the study explain that the role of Kodim 0705/Magelang in improving nationalism among students is quite good, especially at SMK Ma`arif Ngluwar Magelang, although there are obstacles that hinder, regarding coordination problems between babinsa and the school, communication problems. The problem can be solved by working together between the school and the Kodim unit. So that the implementation of national insight that will be given by the military personnel is carried out well and there are no problems.